1999
DOI: 10.1074/jbc.274.50.35963
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Phosphatidylinositol 3-Kinase Lipid Products Accumulate upon Oxidative and Osmotic Stress and Lead to Different Cellular Responses

Abstract: Signaling by phosphatidylinositol (PI) 3-kinases is mediated by 3-phosphoinositides, which bind to Pleckstrin homology (PH) domains that are present in a wide spectrum of proteins. PH domains can be classified into three groups based on their different lipid binding specificities. Distinct 3-phosphoinositides can accumulate upon PI 3-kinase activation in cells in response to different stimuli and mediate specific cellular responses. In Swiss 3T3 mouse fibroblasts, oxidative stress induced by 1 mM H 2 O 2 cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 35 publications
4
101
0
2
Order By: Relevance
“…However, it is not clear how widely this can be applied across a variety of tyrosine phosphorylation-dependent signaling pathways. The examination of PI-3 kinase activity has demonstrated that the increase of PI-3 kinase activity in both SK-N-SH and SK-N-BE(2) cells is much lower in response to exogenous H 2 O 2 (Ͻ2-fold) than insulin (Ͼ7-fold) as noted in a previous report (Van der Kaay et al, 1999). This result suggests that exogenous oxidant is less effective than insulin stimulation in the activation of PI-3 kinase.…”
mentioning
confidence: 70%
“…However, it is not clear how widely this can be applied across a variety of tyrosine phosphorylation-dependent signaling pathways. The examination of PI-3 kinase activity has demonstrated that the increase of PI-3 kinase activity in both SK-N-SH and SK-N-BE(2) cells is much lower in response to exogenous H 2 O 2 (Ͻ2-fold) than insulin (Ͼ7-fold) as noted in a previous report (Van der Kaay et al, 1999). This result suggests that exogenous oxidant is less effective than insulin stimulation in the activation of PI-3 kinase.…”
mentioning
confidence: 70%
“…However, the finding that agonists, such as hydrogen peroxide [30], and crosslinking of platelet-integrin receptors [31] elevate PtdIns(3,4)P # , without increasing PtdIns(3,4,5)P $ , suggest that PtdIns(3,4)P # may be able to regulate physiological processes distinct from those controlled by PtdIns(3,4,5)P $ . TAPP1 and TAPP2 ( Figure 3) are the first proteins to be identified that interact with PtdIns(3,4)P # specifically, and may therefore be key mediators of cellular responses that are regulated specifically by this second messenger.…”
Section: Discussionmentioning
confidence: 99%
“…PtdIns(3,4)P 2 functions as a signaling molecule in growth factor-stimulated pathways and also is generated independently of PtdIns(3,4,5)P 3 in response to oxidative stress (Van der Kaay et al, 1999). The major metabolic pathway for PtdIns(3,4)P 2 synthesis in growth factor-stimulated cells is via 5-phosphatase hydrolysis of PtdIns(3,4,5)P 3 .…”
Section: Discussionmentioning
confidence: 99%
“…4,4,5)P 3 ] is a transient plasma membrane (PM) signal, rapidly hydrolyzed to phosphatidylinositol-(3,4)-bisphosphate [PtdIns(3,4)P 2 ] by the inositol polyphosphate 5-phosphatases (5-phosphatases) (Stephens et al, 1993;Mitchell et al, 2002). PtdIns(3,4)P 2 is a more sustained signal lasting for up to 60 min, stimulated by B-cell activation, oxidative stress, or irreversible platelet aggregation (Banfic et al, 1998;Van der Kaay et al, 1999;Marshall et al, 2002).…”
Section: Introductionmentioning
confidence: 99%